IMPORTANCE OF HUMAN RESOURCE MANAGEMENT AND ITS ROLE IN ACHIEVING INSTITUTIONAL EXCELLENCE, UNIVERSITY OF BAGHDAD AS A ROLE MODEL - Assistant Lecturer Ali Muhammad Salem Jassim (Scholars Digest Publishing, 2024)
The purpose of this study is to explore the importance of human resource management at the University of Baghdad and its role in the success of the institution. The study was conducted on a sample of (200) university employees, and data were collected through the distribution of questionnaires. Data were analyzed using the statistical program SPSS. The results indicate that human resource management plays a vital role in the institutional success of the University of Baghdad. Your responsibilities will be to lead and organize work teams, recruit and select qualified employees, deliver ongoing development and training programs, and implement reward and incentive policies. Furthermore, the study links the performance and achievement of recovery goals of universities to various human resource management principles. The study recommends improving recruitment and personnel selection policies, providing ongoing development and training programs, promoting a culture of teamwork, and implementing reward and incentive policies. We also recommend promoting a culture of innovation and creativity and achieving a work-life balance for employees.
Keywords: Human Resources Management Strategy, Institutional Excellence, University of Baghdad